2007
DOI: 10.1186/ar2274
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine prevents in vitro collagen degradation in chondrocytes by inhibiting advanced lipoxidation reactions and protein oxidation

Abstract: Osteoarthritis (OA) affects a large segment of the aging population and is a major cause of pain and disability. At present, there is no specific treatment available to prevent or retard the cartilage destruction that occurs in OA. Recently, glucosamine sulfate has received attention as a putative agent that may retard cartilage degradation in OA. The precise mechanism of action of glucosamine is not known. We investigated the effect of glucosamine in an in vitro model of cartilage collagen degradation in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 52 publications
0
33
0
1
Order By: Relevance
“…Clinically, an increased level of MDA is observed in the corneas of patients suffering from keratoconus and bulloskeratopathy. It also can be found in tissue sections of joints from patients with osteoarthritis [123,124].…”
Section: Malondialdehydementioning
confidence: 96%
“…Clinically, an increased level of MDA is observed in the corneas of patients suffering from keratoconus and bulloskeratopathy. It also can be found in tissue sections of joints from patients with osteoarthritis [123,124].…”
Section: Malondialdehydementioning
confidence: 96%
“…The effect, however small, may be due to an increase in collagen production by chondrocytes in the supplemented groups. 22 Tiku et al 23 showed that treatment of chondrocytes with a similar concentration of glucosamine prevents in vitro collagen degradation over time. More likely, the higher collagen content may reflect the fact that the supplemented group was stiffened because of a rise in PG content and yielded less matrix damage.…”
Section: Discussionmentioning
confidence: 99%
“…One in vitro study reported the effect of glucosamine hydrochloride and glucosamine sulphate on collagen degradation induced by calcium ionophore-activated chondrocytes (Tiku et al, 2007). The Panel considers that the evidence provided does not establish that an effect of glucosamine on the degeneration of collagen in this in vitro model can predict an effect on cartilage degeneration in humans.…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 98%